Piscicultura do oeste do Paraná: o desenvolvimento endógeno e neoendógeno, e a promoção do desenvolvimento rural sustentável - Brenzan , Cinara Kottwitz Manzano (2023)
The present thesis has as main constitutive elements of the sustainable rural development of fish farming in the western region of Paraná the endogenous elements and endogenous and neoendogenous elements, which emerged through the inductive analytical synthesis. The endogenous evidences emotional involvement, rural organization, assumed risks and opportunities. As for endogenous and neoendogenous development acting together, they gave rise to learning, technology, environmental legislation and health, public policies and commercialization. assumed risks and opportunities. This thesis is arranged in 4 articles, which were integral parts of the theoretical and practical maturation of the path taken around the analyzed object. Article 1, presents a representation of fish farming in the western region of Paraná and Brazil. Aquaculture in Brazil represents one of the productive activities of fundamental importance for economic growth and human nutrition. However, information and characterization of the activity are still scarce in the Brazilian context. This research aims to contribute to this issue by analyzing data from Brazilian fish farming, showing tilapia production in the main cities, mesoregions and states volved in its production. Article 2, aims to analyze the historical aspects of the development of fish farming in Western Paraná. There is a lack of scientific studies that bring together historical elements. In order to fill this gap, the study applied a methodology that made it possible to expand the record of experiences of those interviewed. In this way, the oral history approach was used, as it allows covering a number of reports about facts not recorded by another type of documentation, with the aim of complementing what is in the documentary records. Article 3, aims to understand the constituent elements of Sustainable Rural Development through a metasynthesis. Aiming to minimize this gap within the Sustainable Rural Development theme, it is considered that this field, since its original conception, has undergone different interpretations and conceptualizations about "development". This study uses metasynthesis as an approach, which is based on qualitative data from case studies carried out previously, that is, the results achieved in each of the cases become part of the primary data of the meta-synthesis research, which will be interpreted together in pursuit of theoretical advancement. Finally, article 4 which details the thesis, was developed with the aim of understanding the constituent elements of sustainable rural development of fish farming in western Paraná. Sustainable Rural Development still lacks research that conceptualizes the elements that constitute it. Sustainable Rural Development still lacks research that conceptualizes the elements that constitute it. This study aims to contribute to this discussion by generating theory from fish farming data in western Paraná. Regarding the design of this research, the onto-epistemological alignment is in line with the anti-structuralist organizational theorizing approach.